Who Are The Tourists? - PETR, Christine (E-Journal of Tourism, 2020)
Tourism is the subject of much research and evaluation at the national or international level. however, tourism remains under-theoretical and defining tourism has long been a challenge for those studying this field. Whether it is a question of quantifying flows, measuring the importance of recurrent and emerging practices, or identifying motivations for choosing destinations and activities, one of the priorities is to be able to accurately identify the subject of study. Purpose of the study are to review (i) who is the author of these so-called "tourist" trips and stays?, and (ii) who can be classified as a tourist? method is based on on the review of some literatures related to the topic. The results show that contextualized and recalled the definitions of tourists based on the recommendations made since IRTS 2008 by the supranational organization for the promotion of tourism on a global scale. Keywords: foreigners, holiday makers, visitors, multicultural exchanges